1994
DOI: 10.1128/iai.62.12.5576-5580.1994
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae recombinant Pfs25 adsorbed to alum elicits antibodies that block transmission of Plasmodium falciparum

Abstract: Antibodies to Pfs25, a cysteine-rich 25-kDa protein present on the surface ofPlasmodiumfalciparum zygotes, can completely block the transmission of malaria parasites when mixed with infectious blood and fed to mosquitoes through a membrane feeding apparatus. Recently, a polypeptide analog, Pfs25-B, secreted from recombinant Saccharomyces cerevisiae was found to react with conformation-dependent, transmission-blocking monoclonal antibodies and to elicit transmission-blocking antibodies in experimental animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 15 publications
1
47
0
Order By: Relevance
“…This suggests that those proteins are synthesized in the appropriate conformations in the DNA vector. Previous studies have shown this to be a critical factor in eliciting TrB antibodies (14).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This suggests that those proteins are synthesized in the appropriate conformations in the DNA vector. Previous studies have shown this to be a critical factor in eliciting TrB antibodies (14).…”
Section: Discussionmentioning
confidence: 95%
“…This was especially important for the use of Pfs25 as an immunogen since previous studies have clearly established that disulfide-bonded conformational epitopes on Pfs25 are targets of TrB antibodies (3). In fact, E. coli-derived recombinant Pfs25 protein could not elicit complete TrB antibodies in mice since it did not recreate the known conformational epitope(s) that is the target of TrB MAbs (14). The only forms of rPfs25 shown to be effective have been those expressed in vaccinia virus or in yeast (3,9,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will be particularly so for antibodies to the EGF-like domain. Whereas the EGFlike domain of MSP1 has been expressed in a conformationally correct form in E. coli (11), it has been necessary to express other proteins containing EGF-like domains in yeast (4,22). It would appear from these studies that MSP4 will require the use of DNA immunization approaches or appropriate eukaryotic host-vector combinations.…”
Section: Discussionmentioning
confidence: 99%